Performance of a state-of-the-art DAC system for FDM readout - den Hartog, R; van Leeuwen, B.-J; Peille, P; van der Kuur, J; Ravera, L; van Loon, D; Jackson, B; den Herder, J.-W (SPIE, 2018)
The 96 read-out chains which are foreseen in the X-ray Integral Field Unit (XIFU) on ESA's L2 mission Athena to receive the signals from the 3840 X-ray microcalorimeter transition-edge sensors (TES), are based on the principle of Frequency Domain Multiplexing (FDM) with closed-loop baseband feedback (BBFB) to match the dynamic range of the read-out to that of the detectors. The XIFU instrument concept currently undergoes a Phase-A assessment. The Digital-to-Analogue Converters (DACs) which generate the carrier signals of the FDM and the signals of the BBFB loops were identified as critical elements. In this presentation we formulate the dynamic range requirements for the DACs and assess to what extend a current state-of-the-art system, based on Analog Devices AD 9726, meets these requirements. In this context, the need to place resonance frequencies on an exact grid, possibly with the assistance of frequency tuning PID loops, or increased accuracy of the lithographic production of the LC bandpass filters used in FDM, is discussed. Finally, the impact of pulse shape, in particular electrical bandwidth, on DAC performance is assessed.